NANOMATERIAIS ELETRÓDICOS A BASE DE CARBONO COM Ni(II)(PAN)2 PARA OXIDAÇÃO ELETROQUÍMICA DE ETANOL EM MEIO ALCALINO - Freire, André da Silva (2011)
This work presents a comparative study of Black Pearls 2000 (BP) and Vulcan XC-72R (obtained concerning the oxidation of ethanol, the nanomaterial Ni(II)(PAN)2/(VC) presented higher values of current than the Ni(II)(PAN)2/(BP). A heat treatment study was carried out for the nanocomposite Ni(II)(PAN)2/(VC) because this material has shown the highest current densities for ethanol oxidation. This material was heat treated (500, 600 and 700 °C), characterized and tested for electrochemical oxidation of ethanol, and compared with the nanocomposite prepared at 25 °C. The heat treatment showed significant influence on properties such as morphology, particle size of both the support and the metal structure, and electrocatalytic activity. The nanocomposite treated at 500 °C showed better performance for electrocatalytic oxidation of ethanol (VC) nanomateriais, used as support for the complex Ni(II)(PAN)2. The composites synthesized were characterized by the following techniques: Transmission Electron Microscopy (TEM), X-ray diffraction and Cyclic Voltammetry. The results showed that the carbon support Vulcan XC-72R, is more porous than the Black Pearls 2000 and both have approximately, the same average particle size. Voltammetric analysis showed that the nanocomposite Ni(II)(PAN)2 presented lower separation between the anodic and cathodic peak potential (ΔEp) , for the pair Ni2+ / Ni3+, than the Ni(II)(PAN)2, however Ni(II)(PAN)2 presented less current density, for this redox couple. The electrocatalytical activity of the two nanocomposites through ethanol oxidation was evaluated by the techniques cyclic voltammetry and chronoamperometry. For the cyclic voltammetric study, Ni(II)(PAN)2/(BP) presented a maximum oxidation for the ethanol at 0.5 V while Ni(II)(PAN)2/(VC) showed a maximum oxidation at 0.6 V, in sodium hydroxide solution 1 mol L-1 with a concentration of 0.137 mol L-1 ethanol. Considering the current densities.